English: English - Fakhran Ramadhan (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
Bali is known as one of the most popular destinations for domestic and international tourists. Beyond its beauty, Reclamation of Benoa Bay in Bali has become a rising controversial issue amongst local people, including the fishermen who live in coastal areas. This reclamation is a problematic issue since such action is considered to be a violation of Balinese local customs. Moreover, the reclamation is also believed to be destructing the local environment. A voice of rejection over this Reclamation plan has emerged since 2012 and it continues to grow among the locals, including amongst artists and musicians from and beyond Bali. The voice of rejection has resulted in the emergence of a compilation track album entitled Bali Menolak (Bali Rejects (Reclamation)) and it aims to increase awareness of the current environmental issues and social injustices occurring in Bali. Influenced by this issue, the writer intends to investigate the ideas of environmental activism of the compilation track album Bali Menolak and its impact.